Fine particulate matter exposure and medication dispensing during and after a coal mine fire: A time series analysis from the Hazelwood Health Study. (March 2019) - Johnson, Amanda L.; Dipnall, Joanna F.; Dennekamp, Martine; Williamson, Grant J.; Gao, Caroline X.; Carroll, Matthew T.C.; Dimitriadis, Christina; Ikin, Jillian F.; Johnston, Fay H.; McFarlane, Alexander C.; Sim, Malcolm R.; Stub, Dion A.; et al.
Abstract: Limited research has examined the impacts of coal mine fire smoke on human health. The aim of this study was to assess the association between prolonged smoke PM2.5 exposure from a brown coal mine fire that burned over a seven week period in 2014 and medications dispensed across five localities in South-eastern Victoria, Australia. Spatially resolved PM2.5 concentrations were retrospectively estimated using a dispersion model coupled with a chemical transport model. Data on medications dispensed were collected from the national Pharmaceutical Benefits Schedule database for 2013–2016. Poisson distributed lag time series analysis was used to examine associations between daily mine fire-related PM2.5 concentrations and daily counts of medications dispensed for respiratory, cardiovascular or psychiatric conditions. Factors controlled for included: seasonality, long-term trend, day of the week, maximum ambient temperature and public holidays. Positive associations were found between mine fire-related PM2.5 and increased risks of medications dispensed for respiratory, cardiovascular and psychiatric conditions, over a lag range of 3–7 days. A 10 μg/m 3 increase in coal mine fire-related PM2.5 was associated with a 25% (95%CI 19–32%) increase in respiratory medications, a 10% (95%CI 7–13%) increase in cardiovascular medications and a 12% (95%CI 8–16%) increase in psychiatric medications dispensed. These findings have the potential to better prepare for and develop more appropriate public health responses in the event of future coal mine fires. Graphical abstract: Image 1 Highlights: This is the first known study to assess the relationship between coal mine fire smoke PM2.5 and medications dispensed. Coal mine fire PM2.5 smoke exposure was associated with increased medications dispension. Future public health preparedness and responses to mine fires should incorporate these findings. Abstract : Coal mine fire smoke PM2.5 particulate exposure was associated with increased dispensing of medications for cardiovascular, respiratory and psychiatric conditions.